Construction of a Novel Method of Measuring Thermal Conductivity for Nanostructures - Ikeda, Hiroya; Yoshida, Shoma; Suzuki, Yuhei; Manimuthu, Veerappan; Salleh, Faiz; Kuwahara, Fujio; Shimomura, Masaru; Murakami, Kenji (Makara Journal of Technology, 2015)
With the aim of characterizing the thermal conduction in a nanometer-scaled materials, we have constructed a novel method on the basis of an ac calorimetric method. In this method, periodic sample heating is performed by light irradiation and the corresponding periodic temperature is detected by infrared irradiative thermometer. This makes us measure the thermal diffusivity out of contact with the objective sample. In the present study, we confirm to measure the thermal diffusivity of bulk Si and Cu by this non-contact method with halogen-lamp irradiation. In determining the thermal diffusivity from the relationship between distance deviation and delay time, the simplest wave equation is used, and the obtained values of thermal diffusivity for Si and Cu are close to those reported. Therefore, this non-contact method is useful for evaluating the thermal conduction and applicable for nanometer-scaled materials by improving local heating and local detecting systems.